Hyponatraemia in the first week of life in preterm infants. Part I. Arginine vasopressin secretion. Issue 5 (May 1984) - Rees, L; Brook, C G; Shaw, J C; Forsling, M L
Abstract : Continuous sequential urinary arginine vasopressin measurements in 14 preterm, ventilated infants suggest that both osmoreceptor and volume receptor systems are able to stimulate the prolonged secretion of arginine vasopressin from 26 weeks' gestation. The kidney is able to respond to arginine vasopressin stimulation from the first day of life and from 26 weeks' gestation. A maximum urine osmolality not exceeding 550 mOsm/kg was reached which varied with hydration of the infant. Excretion of arginine vasopressin and urine osmolality increased during deterioration of respiratory illness, mask ventilation, bilateral pneumothoraces, and severe intraventricular haemorrhage. The data show that inappropriate arginine vasopressin secretion is common during illness in the first week of life in preterm infants and that strict attention must be paid to water balance during this time.